P251 Treatment dilemma of chlamydia in pregnancy. (18th May 2015) - Thomas, Jemy; Bates, CM; Mathew, T
Abstract : Background: Drug hypersensitivity reactions are immunological responses to medications. An accurate understanding of the type of antibiotic hypersensitivity reactions is crucial in the decision making process of alternative antibiotic usage versus desensitisation. Clinical presentation: A 25-year old female, twenty-four weeks pregnant, with dysuria was diagnosed with Chlamydia. She had asthma, which was treated with inhalers. She gave a history of reaction to penicillin and an episode of collapse and rash to erythromycin. Effective treatments for Chlamydia are azithromycin, erythromycin, amoxicillin and doxycycline. The latter is contraindicated in pregnancy and erythromycin and amoxicillin were contraindicated because of this patient's history. There is small risk of cross reactivity between azithromycin and erythromycin, so a desensitisation protocol was drawn up by the immunologist. The patient was counselled regarding the possibility of a reaction even to small doses of azithromycin and the possibility of an anaphylactic reaction needing adrenaline, which could precipitate preterm labour. She was admitted on the ward and given azithromycin in titrating doses, which was tolerated well without any problems. The repeat chlamydia test following treatment was negative. Discussion: There are limited therapeutic choices for treatment of various sexually transmitted infections in patients with allergies particularly in pregnancy. These patients will need desensitisation under an immunologist with careful monitoring. If a patient with a reported allergy is deemed not allergic or if the allergy is simply an expected side effect, the medical record should be updated to reflect this change along with educating the patient.